2021
DOI: 10.3390/ijerph18157732
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Changes in Health Behaviors and Depressive Symptoms during the COVID-19 Pandemic: A Longitudinal Analysis from Pre-pandemic to Onset and End of the Initial Emergency Conditions in Finland

Abstract: The COVID-19 pandemic and social distancing measures targeting the transmission of the virus impacted everyday life in 2020. This study investigated pre- to in-pandemic changes in health behaviors and depressive symptoms during the COVID-19 pandemic and the role of personality traits in these changes in Finland. Data from a larger population-based cohort study of 51–59-year-old Finnish women were used (n = 358). Self-reported questionnaires gathered information about depressive symptoms, eating behavior, physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 54 publications
2
19
1
Order By: Relevance
“…An increase in total AUDIT-C scores during the pandemic compared to pre-COVID-19 was shown in a sample of vulnerable groups (people with self-reported mental health problems) ( 50 ). While an increased alcohol consumption during the pandemic, as found in our study, was reported by several other studies ( 51 ), a decreased or unchanged consumption was also observed ( 52 , 53 ). The inconsistent results may be explained by the differences in study population as well as measurement time (beginning of the pandemic etc.)…”
Section: Discussionsupporting
confidence: 89%
“…An increase in total AUDIT-C scores during the pandemic compared to pre-COVID-19 was shown in a sample of vulnerable groups (people with self-reported mental health problems) ( 50 ). While an increased alcohol consumption during the pandemic, as found in our study, was reported by several other studies ( 51 ), a decreased or unchanged consumption was also observed ( 52 , 53 ). The inconsistent results may be explained by the differences in study population as well as measurement time (beginning of the pandemic etc.)…”
Section: Discussionsupporting
confidence: 89%
“…Putting the findings to a broader context, Finland, being a Nordic welfare state, is characterised by efficient public health care services and social welfare to ensure peoples wellbeing and financial livelihood [ 12 ]. Finally, why some older people reacted more positively to the pandemic than others may be explained by certain personality traits, e.g., higher extraversion, and psychosocial resources, e.g., better stress-coping ability, as suggested before [ 37 39 ].…”
Section: Discussionmentioning
confidence: 85%
“…In the European studies analyzed, the female gender was found to be significantly more at risk than the male for the development of stress and anxiety, depression [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ], and post-traumatic symptoms [ 79 , 80 , 81 ]. The evolution of symptoms over time was also worse for women [ 82 ].…”
Section: Resultsmentioning
confidence: 99%